Alterações eletroneuromiográficas em idosos com estenose de canal raquídeo lombar degenerativa: associação com as alterações de imagem e clínica - Ziegler, Marcus Sofia (2012)
The aim of this study is to identify the role of EMG-NCS on LSS diagnosis. A cross-sectional study with prospective data collection was conducted involving 31 symptomatic patients with LSS confirmed by MRI. All patients reported pain, 83.9% of patients reported it to be moderate or severe and 90% of patients took pain medication. LSS did not affect NCS or SSR. EMG confirmed high frequency of radiculopathy, particularly multiradiculopathy. L5 and S1 roots were the most susceptible to injuries. We also found a higher prevalence of L4 radiculopathy. Correlating EMG with clinical findings, we found that the clinical presentation, the most important starting point of an evaluation, is poor in terms of identifying radiculopathy, a frequent consequence of LSS. For this reason, we theorize that EMG may play an important role as a diagnostic tool, being useful in determining when symptoms are neurogenic in nature. In addition, it may serve to focus treatment only in the area where it is really necessary.